PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA PADA BAGIAN PRODUKSI PUSRI 1B PT. PUPUK SRIWIDJAJA PALEMBANG - Syafarudin Syafarudin; Omar Hendro; Muhammad Wadud (Universitas Indo Global Mandiri)
The purpose of this study was to determine how much influence the health and safety on the performance of employees At Pusri Operations Division 1B PT. Pupuk Sriwidjaja Palembang. The number of members of a population of as many as 150 employees. The sampling technique using simple random sampling since the sampling is done at random members of the population regardless of strata that exist in the population. And the determination of the sample size in this study using a formula Slovin, in order to obtain the results of 60 respondents to be sampled in the study. This research uses descriptive analysis with quantitative approach using a questionnaire as a data collection tool and using the technique of simple linear regression analysis to measure the impact of independent variables on the dependent variable is the occupational safety and health as an independent variable (X) and employee performance as the dependent variable (Y ). The data in this study aided by Stastitical program for Product and Service Solution (SPSS) version 22. The results of this study stated that the safety and health significant and positive impact on the performance of employees of PT. Pupuk Sriwidjaja Palembang. Based on the results of empirical testing of safety and health variables have 0.544dengan coefficient value of 8.321 t value as well as the significant value of 0.000.Key words: Occupational Health and Safety, Employee Performance